2013
DOI: 10.1128/jcm.01337-13
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Small-Colony Variants of Ornithobacterium rhinotracheale

Abstract: bOrnithobacterium rhinotracheale is a Gram-negative bacterium associated with respiratory diseases in many avian species, with worldwide distribution, and it causes significant economic loss to the poultry industry. In this study, the isolation and characterization of O. rhinotracheale small-colony variants (SCVs) are described for the first time. O. rhinotracheale isolates (n ‫؍‬ 27) were recovered from tracheal samples (n ‫؍‬ 321) collected from different avian species with clinical signs of respiratory dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…A study from China reported that small-colony variants, had overall higher MICs levels compared with their wild-type counterparts. Differences were also found with regards to other phenotypic characteristics, but not in their genotype ( 79 ).…”
Section: Methodsmentioning
confidence: 88%
“…A study from China reported that small-colony variants, had overall higher MICs levels compared with their wild-type counterparts. Differences were also found with regards to other phenotypic characteristics, but not in their genotype ( 79 ).…”
Section: Methodsmentioning
confidence: 88%
“…The production (expression) of a hemagglutinin and neuraminidase have been described in ORT [50]. These virulence factors may play an important role in tissue colonization and inflammation in the host [51]. In addition, although ORT hemolysin may also act as a virulence factor, recent studies The production (expression) of a hemagglutinin and neuraminidase have been described in ORT [50].…”
Section: Clinical Signs and Pathological Lesionsmentioning
confidence: 99%
“…In addition, although ORT hemolysin may also act as a virulence factor, recent studies The production (expression) of a hemagglutinin and neuraminidase have been described in ORT [50]. These virulence factors may play an important role in tissue colonization and inflammation in the host [51]. In addition, although ORT hemolysin may also act as a virulence factor, recent studies have shown that non-hemolytic isolates can survive longer in the host and present high pathogenicity [52].…”
Section: Clinical Signs and Pathological Lesionsmentioning
confidence: 99%
“…The assay was performed according to the manufacturer's recommendations. Auxotrophism of SCVs for haemin, menadione and thymidine was assessed with the use of the disc method (Zahra et al, 2013). Bacteria were considered auxotrophic when they demonstrated increased growth around the impregnated disc as compared to the periphery.…”
Section: Isolation and Identification Of Bacteriamentioning
confidence: 99%